2009
DOI: 10.1007/s11214-009-9523-8
|View full text |Cite
|
Sign up to set email alerts
|

GP-B Systematic Error Determination

Abstract: We have evaluated the systematic error in the GP-B experiment using five different approaches and estimated the individual contributions of many error sources. The systematic effects we consider include those due to gyroscope torques, gyroscope readout, telescope readout, and guide star proper motion. Effects with an estimated impact on the experiment error larger than 1 mas/yr are discussed in detail. Examples of analyses that bound other sources to less than 1 mas/yr are included to show the range of techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Such a figure is greater than the previously expected 1% level because of a number of unwanted systematic errors whose proper treatment required much additional efforts by the GP-B team [10]. Independent analyses by different teams will be important in critically assessing the reliability of the results of [7].…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Such a figure is greater than the previously expected 1% level because of a number of unwanted systematic errors whose proper treatment required much additional efforts by the GP-B team [10]. Independent analyses by different teams will be important in critically assessing the reliability of the results of [7].…”
mentioning
confidence: 89%
“…The Gravity Probe B (GP-B) experiment [6] officially came to an end, with the release of its final results [7] according to which the general relativistic gravitomagnetic gyroscope precession [8,9] would have been measured with a claimed accuracy of 19%. Such a figure is greater than the previously expected 1% level because of a number of unwanted systematic errors whose proper treatment required much additional efforts by the GP-B team [10]. Independent analyses by different teams will be important in critically assessing the reliability of the results of [7].…”
mentioning
confidence: 89%
“…The accompanying paper "GP-B Systematic Error" (Muhlfelder et al 2009) reviews the current limits. More than a hundred uncertainty sources have been considered using five different classes of evaluation technique: (1) the spread in relativity estimates from the four gyroscopes; (2) studies of different partial data sets at different times of year; (3) comparisons between physics-based models of possible disturbances with appropriate sections of on-orbit data; (4) sensitivity testing by propagating modified values of disturbances (e.g.…”
Section: The Evolving Data Analysis Processmentioning
confidence: 99%
“…The interferometric free-fall experiments by Luo & et al (2002) and Zhou & et al (2002) again found null results in disagreement with (Hayasaka & Takeuchi, 1989). For rotating bodies, the ultraprecise Gravity Probe B experiment (Everitt & et al, 2009, Heifetz & et al, 2009, Keiser & et al, 2009, Muhlfelder & et al, 2009, Silbergleit & et al, 2009, which measured the frame-dragging effect and geodetic precession on four quartz gyros, has the best accuracy. GP-B serves as a starting point for the measurement of the gyrogravitational factor of particles.…”
Section: Introductionmentioning
confidence: 98%
“…At present, the variety of consequences of the precision experiments from astrophysical observations makes it possible to probe this fundamental issue more deeply by imposing the constraints of various analyzes. Currently, the observations performed in the Earth-Moon-Sun system (Everitt & et al, 2009, Faller & et al, 1990, Gabriel & Haugan, 1990, Gillies, 1997, Haugan & Kauffmann, 1995, Hayasaka & Takeuchi, 1989, Heifetz & et al, 2009, Imanishi & et al, 1991, Keiser & et al, 2009, Luo & et al, 2002, Muhlfelder & et al, 2009, Ni, 2011, Nitschke & Wilmarth, 1990, Quinn & Picard, 1990, Silbergleit & et al, 2009, Turyshev, 2008, Will, 2006, Zhou & et al, 2002, or at galactic and cosmological scales (Haugan & Lämmerzahl, 2001, Lämmerzahl & Bordé, 2001, Ni, 2005a,b,c, 2008, probe more deeply both WPE and strong EPE. The intensive efforts have been made, for example, to clear up whether the rotation state would affect the trajectory of test particle.…”
Section: Introductionmentioning
confidence: 99%